Comparison of The Effects of Rocuronium Bromide And Cis-Atracurium Besylate on Intubating Conditions And Haemodynamic Response - Sreelal, Parvati; Sen, Jayashree; Singam, Amol (International Journal of Psychosocial Rehabilitation, 2020)
Background/rationale: Safe and rapid endotracheal intubation is of cardinal importance in general anaesthesia. The ease of endotracheal intubation depends on a multitude of factors like degree of muscle relaxation, depth of anaesthesia and skill of the intubating anaesthesiologist. The haemodynamic effects like tachycardia, hypertension[1] is initiated within 5 s of laryngoscopy, peaks in 1–2 min and returns to normal levels by 5 min. It can incite harmful effects such as myocardial ischaemia, ventricular dysrrhythmias, ventricular failure and pulmonary oedema which is attenuated by the use of drugs like Lignocaine, Dexmedetomidine. [2,3,4,5,6]. Cisatracurium besylate is a bisbenzyl- tetrahydro-isoquinoliniumn, in the category of non-depolarizing neuromuscular intermediate in its onset and duration of action. Cisatracurium degrades spontaneously at physiological pH via Hofmann elimination to yield an active laudanosine and the quaternary monoacrylate . [7]The recommended maintenance dose of Cis-atracurium is 0.03 mgkg–1 ,following 40-50 min after the intubating bolus dose of 0.15 mgkg–1 . Rocuronium bromide is structurally a 2 morpholino 3-disacetyl 16 N-allyl pyrrolidino derivative of thenon depolarizing muscle relaxant, vecuronium. The recommended intubating dose in general anaesthesia is 0.6mg per kg body weight, after which clinically acceptable intubation conditions are established within 60 seconds in nearly all patients. The recommended maintenance dose is 0.15mg per kg body weight but in the case of use of inhalational anaesthesia for a long duration, this should be reduced to 0.075-0.1mg per kg body weight. Neostigmine or Suggamadex can be used as the reversal agent. Objectives: The objectives are to compare the intubating conditions of rocuronium and cis- atracurium and haemodynamic stability of these agents during intubation. Any side effects are noted